G161(P) The best practice tariff in paediatric diabetes –patient views and preferences. (24th May 2017) - Newton, R; Dunn, S; Neail, C; Brown, C; Diegnan, J; Thalava, R; Puttha, R
Abstract : Aims: The Best Practice Tariff (BPT) for paediatric diabetes set minimum standards of care for children with diabetes. BPT criteria include expert support within 24 hours of diagnosis, a structured diabetes education programme, four multi-disciplinary (MDT) clinic appointments with eight additional contacts per year, an annual dietetic appointment, quarterly HbA1C measurements, annual psychiatric assessments, 24 hour expert advice and support for high HbA1c. This project investigated the preferences of patients and their parents at a small general hospital regarding BPT criteria. Methods: A questionnaire was given to patients during diabetic outpatient clinics in November 2016. The survey asked patients to rate the services they received and to make suggestions on how the services could be improved. Results: Twenty-seven questionnaires were returned. 89% of respondents felt the diabetes education they received was very useful or useful. 58% felt education updates should be half-yearly with 30% preferring 3 monthly. The majority of respondents (80%) felt clinic appointments should occur quarterly, with 14% preferring 2 monthly appointments and 6% half-yearly. 93% expressed a preference to see multidisciplinary team together during these appointments. The preferred frequency of contact from the team was 2 monthly (68%) with 32% of respondents wishing to be contacted monthly. Electronic methods of communication such as telephone (31%), email (22%) and text message (20%) were preferred to face-to-face meetings (16%) or school visits (10%). While 60% of respondents felt 'satisfied' or 'very satisfied' with the psychological support they had received for their diabetes, a quarter expressed dissatisfaction with the delay in accessing these services. 85% of the respondents were aware of the availability of 24 hour advice service. When the HbA1C was higher than the recommended 48 mmol/mol of IFCC, 88% of the patients preferred close support and contact by telephone or text and 12% suggested more frequent clinic appointments. Conclusion: Clinic frequency and patient contacts mandated by the BPT largely correlate with the preferences of patients and families. Electronic methods of contact are preferred. Psychological services carry higher rates of patient dissatisfaction. When HbA1C is higher than recommended patients prefer more frequent contacts. The underlying reasons warrant further study to improve patient experiences.